Concomitant Small Cell Neuroendocrine Carcinoma of Gallbladder and Breast Cancer. (25th September 2014) - Aiello, Paolo; Aragona, Francesco; Territo, Valentina; Caruso, Anna Maria; Patti, Rosalia; Buscemi, Salvatore; Di Vita, Gaetano
Abstract : The neuroendocrine carcinoma is defined as a high-grade malignant neuroendocrine neoplasm arising from enterochromaffin cells, usually disposed in the mucosa of gastric and respiratory tracts. The localization in the gallbladder is rare. Knowledge of these gallbladder tumors is limited and based on isolated case reports. We describe a case of an incidental finding of small cell neuroendocrine carcinoma of the gallbladder, observed after cholecystectomy for cholelithiasis, in a 55-year-old female, who already underwent quadrantectomy and sentinel lymph-node biopsy for breast cancer. The patient underwent radiotherapy for breast cancer and six cycles of chemotherapy with cisplatin and etoposide. Eighteen months after surgery, the patient was free from disease. Small cell neuroendocrine carcinoma of the gallbladder has poor prognosis. Because of the rarity of the reported cases, specific prognostic factors have not been identified. The coexistence of small cell neuroendocrine carcinoma of the gallbladder with another malignancy has been reported only once. The contemporary presence of the two neoplasms could reflect that bioactive agents secreted by carcinoid can promote phenotypic changes in susceptible cells and induce neoplastic transformation.